Factors influencing the orthodontic treatment duration at dental teaching hospitals - Nahidh Mohammed; Ali Saif Mauwafak; Al-Groosh Dheaa H. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2023)
Introduction: One of the primary worries of orthodontic patients, aside from the final results, is the total period of treatment. A superior comprehension of orthodontic treatment period just as variable influencing the treatment length is valuable for productive patient guiding and improved clinical performance. The aim of the study was analysis of factors influencing the length of treatment of finished cases treated with fixed orthodontic appliance at the dental teaching hospital in the College of Dentistry/ University of Baghdad. Materials and Methods: Eighty case sheets belonging to 80 finished orthodontic cases (forty finished with a single operator and forty finished with multi-operators) were selected from the archive of the orthodontic department to collect six parameters, namely duration of treatment, number of supervisors, number of visits, type of malocclusion, treatment method, presence or absence of crossbite. Chi-square test was used to test group differences and to study the association between the duration of treatment and the types of malocclusion with the indication for dental extraction in both groups. Results: The results showed highly significant group difference regarding all parameters except the presence or absence of crossbite. On the other hand, no significant association was found between the type of malocclusion and duration of treatment with the indication of extraction in both groups. Conclusions: The number of supervisors with their different opinions in treating and managing orthodontic cases and the type of malocclusion may be the main contributing factor affecting the treatment duration of the finished orthodontic cases.